Promotion of testa rupture during garden cress germination involves seed compartment-specific expression and activity of pectin methylesterases - Scheler, Claudia; Weitbrecht, Karin; Pearce, Simon P.; Hampstead, Anthony; Büttner-Mainik, Annette; Lee, Kieran J.D.; Voegele, Antje; Oracz, Krystyna; Dekkers, Bas J.W.; Wang, Xiaofeng; Wood, Andrew T.A.; Bentsink, Leónie; et al. (American Society of Plant Biologists, 2015)
Pectin methylesterase (PME) controls the methylesterification status of pectins and thereby determines the biophysical properties of plant cell walls, which are important for tissue growth and weakening processes. We demonstrate here that tissue-specific and spatiotemporal alterations in cell wall pectin methylesterification occur during the germination of garden cress (Lepidium sativum). These cell wall changes are associated with characteristic expression patterns of PME genes and resultant enzyme activities in the key seed compartments CAP (micropylar endosperm) and RAD (radicle plus lower hypocotyl). Transcriptome and quantitative real-time reverse transcription-polymerase chain reaction analysis as well as PME enzyme activity measurements of separated seed compartments, including CAP and RAD, revealed distinct phases during germination. These were associated with hormonal and compartment-specific regulation of PME group 1, PME group 2, and PME inhibitor transcript expression and total PME activity. The regulatory patterns indicated a role for PME activity in testa rupture (TR). Consistent with a role for cell wall pectin methylesterification in TR, treatment of seeds with PME resulted in enhanced testa permeability and promoted TR. Mathematical modeling of transcript expression changes in germinating garden cress and Arabidopsis (Arabidopsis thaliana) seeds suggested that group 2 PMEs make a major contribution to the overall PME activity rather than acting as PME inhibitors. It is concluded that regulated changes in the degree of pectin methylesterification through CAP- and RAD-specific PME and PME inhibitor expression play a crucial role during Brassicaceae seed germination.